Mistreatment in the gynaecology and obstetrics units of health facilities: community women's experiences in Guinea - Sall, Alpha Oumar; Diallo, Ramata; Balde, Mamadou Dioulde; Camara, Sadan; Kourouma, Kabinet; Toure, Madeleine; Diallo, Aissatou; Sidibe, Tiany; Millimono, Felix; Balde, Ousmane (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Improving maternal and child health helps to ensure women's well-being. However, despite many efforts, women are still subjected to mistreatment and abuse in health facilities such as gynaecology and obstetrics units. Data on women's mistreatment in gynaecology are scarce and insufficient in obstetrics departments. This study therefore analyses women's experiences of mistreatment in these services in Guinea. Methods: This study is based on a qualitative approach using in-depth individual interviews and group discussions with community women. The data was subjected to thematic analysis. Results: This study revealed a high prevalence of mistreatment of women in health facilities, both during provision of gynaecological services and in obstetric units (pregnancy, prenatal consultations and childbirth). They are mainly victims of verbal abuse, negligence and informal payment, and to a lesser extent physical violence. Victims generally have few means of redress. This mistreatment is encouraged above all by the lack of training for health care providers, the inadequacy of services and the absence of sanctions. To prevent and combat this phenomenon, it is necessary to organise training courses on respectful maternal care for healthcare providers, make patients aware of their rights and the culture of consent, and apply disciplinary sanctions. Conclusions: This study has enabled us to understand the types and extent of mistreatment suffered by women in obstetrics and gynaecology units. It identified measures to be taken to prevent and combat mistreatment in these units in order to ensure respectful healthcare and improve relations between healthcare providers and their clients.